CLEAR LIGHT OF DAY: A FOCUS ON THE THEMES OF MEMORY AND TIME - Talukder, Md. Jobaar; Biswas, Prakash Chandra (UIN Alauddin Makassar, 2024)
Clear Light of Day, one of the classic works of South Asian writer Anita Desai, focuses primarily on time and memory. In this novel she has skillfully portrayed how time and memory influence the personal and familial life, identities and relationships of individuals. Being set at the backdrop of Old Delhi, the novel reflects the importance of time and memory. Eventually, how time works as destroyer as well as preserver and how significant role memory plays in every individual’s life become the pivotal themes in Clear Light of Day. The novel explores the lives of the members of the Das family through the lenses of time and memory. Desai has used the concept of time of T. S. Eliot who remarks time as the “Destroyer and Preserver” and it has given the novel a profound base. This paper focuses closely on the roles and thematic exploration of time and memory in Clear Light of Day.